The use of complementary medicine methods by the nurses working during the covid-19 pandemic - KARABUĞA YAKAR, HATİCE (My University, 2023)
Objective: This study aimed to determine the use of complementary medicine methods by nurses working on the front line during the Coronavirus disease-2019 (COVID-19) pandemic. Method: The study was planned as a descriptive and cross-sectional type and carried out in a training and research hospital in İstanbul with 208 nurses. Nurse Identification Form and Complementary and Integrative Health Assessment for Health Practitioners Scale were used to collect data. Descriptive statistics, Mann-Whitney U test, Kruskal-Wallis test were used to evaluate the data. Results: The mean age of the nurses was 34.25±6.3 years. 86.5% were women, 76% had a bachelor’s degree, 37% had been working for ten years or more, and 68.8% used complementary medicine methods during the pandemic. In the study, the use of complementary medicine methods was higher in the nurses with a bachelor’s degree, those with an average economic status, those with a family member over the age of 65 who had a chronic disease, those who received training on complementary medicine methods, used complementary medicine methods during the pandemic, and those who recommended complementary medicine methods to their relatives and patients. Conclusion: Complementary integrative health assessment scores of the nurses were above average. The majority used complementary medicine methods and they had an increasing interest in integrating these methods into their professional practices.

Amaç: Bu çalışma Koronavirüs hastalığı-2019 (COVID-19) pandemi sürecinde çalışan hemşirelerin tamamlayıcı tıp yöntemlerini kullanma durumlarını belirlemek amacıyla planlandı. Yöntem: Tanımlayıcı ve kesitsel tipte yapılan bu araştırma, İstanbul’da bir eğitim araştırma hastanesinde 208 hemşire ile yürütüldü. Veri toplama aracı olarak hemşire tanılama formu ve sağlık profesyonelleri için tamamlayıcı ve bütüncül sağlık değerlendirme ölçeği kullanıldı. Verilerin değerlendirilmesinde tanımlayıcı istatistikler, Mann-Whitney U testi, Kruskal-Wallis testi kullanıldı. Bulgular: Yaş ortalaması 34,25±6,3 yıl olan hemşirelerin, %86,5’i kadın, %76’sı lisans mezunu, %37’si on yıl ve üzeri çalışmakta, %68’i pandemi süreci boyunca tamamlayıcı tıp yöntemlerini kullanmaktaydı. Çalışmada lisans mezunu hemşirelerde, ekonomik durumu orta olanlarda, ailesinde 65 yaş üstü kronik hastalığa sahip birey bulunanlarda, tamamlayıcı tıp yöntemleri hakkında eğitim alanlarda, pandemi sürecinde tamamlayıcı tıp yöntemi kullananlarda, tamamlayıcı tıp yöntemlerini yakınlarına ve hastalara önerenlerde tamamlayıcı tıp yöntemlerini kullanma durumlarının daha yüksek olduğu bulundu. Sonuç: Hemşirelerin tamamlayıcı ve bütüncül sağlık değerlendirme puanları ortalamanın üstündeydi. Hemşirelerin çoğunluğu tamamlayıcı tıp yöntemlerini kullanmaktaydı ve bu yöntemleri mesleki uygulamalarına entegre etme konularında ilgilerinin arttığı görüldü.
Covid-19 pandemi sürecinde çalışan hemşirelerin tamamlayıcı tıp yöntemlerini kullanma durumlar
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); hemşirelik; pandemi; tamamlayıcı tıp yöntemleri; COVID-19; nursing; pandemic; complementary medicine methods